Preparasi TiO2 Nanotube Arrays (TNAs) Menggunakan Metode Anodisasi Dua Tahap - Zahara Ramadani; Sherly Kasuma Warda Ningsih (Lembaga Yasin AlSys, 2026)
Titanium dioxide (TiO₂) is a semiconductor material widely used in various ultraviolet-responsive applications; however, the controlled growth of well-ordered and homogeneous TiO₂ nanotube arrays (TNAs) via two-step anodization still requires further investigation. This study aimed to analyze TNA growth, current density behavior, and optical characteristics using a two-step anodization method. The experimental approach was conducted on Ti foil substrates at a constant potential of 50 V for 60 minutes in the first step and 30 minutes in the second step. Current density was recorded throughout the anodization process, while the optical properties of the TNAs were analyzed using UV-Vis Diffuse Reflectance Spectroscopy (DRS) with Tauc plot analysis. The results revealed three main current density phases in the first step, namely an initial decrease from 14 mA/cm² to 10 mA/cm² within 30 seconds, an increase to 11.5 mA/cm² at 120 seconds, and a relatively constant condition thereafter, whereas the second step exhibited a faster and more stable current decrease. The band gap energy of the TNAs was determined to be 3.37 eV, with dominant absorption in the ultraviolet region at around 367.95 nm. These findings confirm the effectiveness of two-step anodization in producing stable and well-ordered TNAs, which can potentially be optimized for various photon-based applications that exploit ultraviolet response.